The financing choices of firms after financial liberalization : Indonesian evidence - Haron, Razali (2016)
The purpose of this study is to evaluate the impact of firm level and three industry level determinants; dynamism, munificence and industry concentration on the capital structure decisions. This study also analyses which capital structure theories better explain the financing decisions of firms in Indonesia. This study employs three regression techniques, the Pooled Ordinary Least Square (OLS), the Fixed Effects and the Random Effects to analyse the relationship between the determinants and the capital structure decisions based on panel data during the period of 2000-2014. Three different definitions of leverage (TD/TA, LTD/TA, STD/TA) have been used to test the robustness of the findings. This study found that large growing firms operating in a highly dynamic environment in Indonesia seem to employ high level of debt and seem to take advantage of the tax shield, reflecting the influence of the trade-off theory. Nevertheless, aged and highly profitable firms with high intangible assets and liquidity level operating in a high munificence environment tend to follow the pecking order theory. This study offers originality and fills the gap by examining the impact of industry characteristics on capital structure which is fairly novel in the study of capital structure especially on emerging market. In addition to that, the significant influence of intangible assets over capital structure decisions as depicted in this study should not be ignored by policy makers in Indonesia.